EFEKTIVITAS PENGGUNAAN APLIKASI E-COURT DALAM PENYELESAIAN PERKARA DI PENGADILAN AGAMA JOMBANG KELAS 1B - Ahmad Azhar Naufal; ibnu Jazari; Nur Hasab (Jurnal Hikmatina, 2022)
This research is motivated by technological developments, especially information technology, which makes it very easy for the public to get information wherever and whenever the Supreme Court as a State Judicial Institution makes innovations in case administration services using e-court applications that have been implemented in Court institutions throughout Indonesia, especially in the Jombang Religious Court Class 1B. The writing of this article uses field research methods, this article tries to explain the use of e-court applications in the Jombang Religious Court Class 1B, the effectiveness of using e-court applications for the Jombang Religious Court Class 1B environment and the general public. The e-court application is an electronic case registration service where the registrant will receive registration, payment, summons and trial information via the registrant’s email. The implementation of the e-court application at the Jombang Religious Court Class 1B is still not effective because there is no obligation for case registrants to register cases electronically. The results showed that the effectiveness of the use of the e-court application at the Jombang Religious Court Class 1B,was not yet ineffective